Preparation method of anti-skid rubber biomass modified three-layer gum dipping anti-chemical coating gloves

By using a mixed fiber composite material of EVA resin and biomass fiber in the chemical-resistant coating, combining coupling agents and accelerators, the sliding glue problem is solved, and the uniform coating and efficient chemical-resistant performance of the gloves are achieved.

CN119144024APending Publication Date: 2024-12-17JIANGSU HANVO SAFETY PROD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411288417.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing chemical-proof coating has slippage between the three layers of glue, resulting in uneven surface coating and cannot meet the standards of chemical-proof, waterproof and air-resistant.

Method used

The resin dispersion of mixed fiber composite materials is prepared by using EVA resin and biomass fiber. Through the three-layer glue impregnation process, combining coupling agents and accelerators, a stable gel structure is formed, which enhances the viscosity and dispersion properties of the latex and reduces slippers. Phenomenon.

Benefits of technology

It achieves uniform distribution and efficient adhesion of latex, improves chemical resistance, enhances the acid and alkali resistance of gloves, and ensures the uniformity and stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144024A_ABST
    Figure CN119144024A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of anti-skid rubber biomass modified three-layer gum dipping anti-chemical coating gloves. The preparation method comprises the following steps: S1, preparing a resin dispersion liquid of a mixed fiber composite material; s2, preparing composite latex; s3, sleeving the glove core on the hand mold, and carrying out preheating treatment; s4, the glove core subjected to preheating treatment is soaked in a coagulating agent; s5, dipping a first layer of composite latex; s6, performing vulcanization treatment for the first time; s7, dipping a second layer of composite latex; s8, carrying out secondary vulcanization treatment; s9, dipping a third layer of composite latex; s10, performing high-temperature vulcanization treatment for the third time; and S11, demolding is conducted, and the anti-skid rubber biomass modified three-layer gum dipping anti-chemical coating glove is prepared. The method has the advantages that on the premise that the original chemical defense performance standard of the butyronitrile gloves is reserved, the EVA resin and the biomass fibers are added to prepare the resin dispersion liquid of the mixed fiber composite material, the problem of rubber slipping is solved, and the chemical defense performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic latex materials, and in particular to a method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating glove. Background Art

[0002] Nitrile latex is made by copolymerizing butadiene and acrylonitrile emulsion. Since the copolymer molecular chain contains nitrile groups, it has good oil resistance and chemical resistance, and has good adhesion to polar substances such as fibers and leather.

[0003] EVA is a thermoplastic elastic resin with excellent performance, mainly in terms of elasticity, flexibility and gloss. In addition, its resistance to environmental stress cracking has been improved, and its tolerance to fillers has been increased. The method of adding more reinforcing fillers can be used to avoid or reduce the decline in EVA's mechanical properties. It can also be modified to obtain new applications.

[0004] High-performance biomass composites provide structural rigidity in applications while also providing good bonding and wear resistance to latex.

[0005] At present, in order to achieve better chemical resistance, chemical resistance coatings generally adopt a three-immersion process. However, there is a phenomenon of glue slippage between the three layers of glue, which leads to uneven coating of the surface coating and fails to meet the chemical resistance, waterproofness and airtightness standards. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing anti-skid rubber biomass modified three-layer dipped chemical protective coating gloves. On the premise of retaining the original performance standard of nitrile gloves for chemical protection, EVA resin and biomass fiber are added to prepare a resin dispersion of a mixed fiber composite material, which solves the problem of slipping rubber and improves the chemical protection performance.

[0007] The above technical objectives of the present invention are achieved through the following technical solutions:

[0008] A method for preparing anti-slip rubber biomass modified three-layer dipped chemical-resistant coating gloves, characterized in that it comprises the following steps:

[0009] S1, blending EVA resin, biomass fiber and coupling agent to form a resin dispersion of a mixed fiber composite material;

[0010] S2, mixing butadiene-acrylonitrile latex, a resin dispersion of a mixed fiber composite material, zinc oxide, an accelerator, a thickener and a color paste to obtain a composite latex;

[0011] S3, taking the glove core and putting it on the hand mold for preheating;

[0012] S4, dipping the preheated glove core into a coagulant;

[0013] S5, dipping the glove core dipped in the coagulant into the first layer of composite latex;

[0014] S6, after a layer of dipped glove core is left to stand, the first vulcanization treatment is performed in an oven;

[0015] S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex;

[0016] S8, after the two-layer dipped glove core is left to stand, a second vulcanization treatment is performed in an oven;

[0017] S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex;

[0018] S10, after the three-layer dipped glove core is left to stand, a third high-temperature vulcanization treatment is performed in an oven;

[0019] S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

[0020] Preferably, the biomass fibers in S1 include flax fibers and corn fibers, the coupling agent is a chelated titanate, specifically di(octyl pyrophosphate)hydroxyacetic acid titanate, and the mass proportions of raw materials added to the resin dispersion of the mixed fiber composite material are: 5-20 parts of EVA resin, 1-10 parts of flax fibers, 1-10 parts of corn fibers and 1-5 parts of coupling agent.

[0021] Preferably, the nitrile latex in S2 is carboxyl nitrile latex, the thickener is a polyacrylic thickener or an associative thickener or hydroxymethyl cellulose or a mixture of the first three in any proportion, the accelerator is ZDEC, and the mass fractions of the raw materials in the composite latex are: 80-120 parts of nitrile latex, 1-20 parts of resin dispersion of mixed fiber composite material, 1-4 parts of zinc oxide, 1-5 parts of accelerator, 4-6 parts of thickener, and 1-2 parts of color paste.

[0022] Preferably, the specific operation of the preheating treatment in S3 includes: placing the glove core in an oven and baking it at 50-70° C. for 10-15 minutes.

[0023] Preferably, the coagulant in S4 is a methanol solution containing 1-5% glacial acetic acid or 1-2% calcium chloride, and the coagulant immersion and homogenization time is 60-90s.

[0024] Preferably, the time for dipping the first layer of composite latex, the second layer of composite latex and the third layer of composite latex in S5, S7 and S9 is 15-25 seconds.

[0025] Preferably, the standing time of the dipped glove core in S6 and S8 is 30 minutes, and the first vulcanization treatment and the second vulcanization treatment are specifically vulcanization in an oven at 60° C. for 30 minutes.

[0026] Preferably, the standing time of the three-layer dipped glove core in S10 is 30 minutes, and the third high-temperature vulcanization treatment is specifically vulcanization in an oven at 80-110° C. for 1-2 hours.

[0027] In summary, the present invention has the following beneficial effects:

[0028] 1. The titanate coupling agent used in the present invention contains four functional groups, with the general formula -RO-Ti-(-OXRY)n-, where RO is a hydrolyzable alkoxy group. X is an atomic group connected to the titanium oxide bond, or a bonding group, which determines the properties of the titanate coupling agent. These groups include alkoxy, carboxyl, sulfoxy, phosphoryloxy, phosphite, pyrophosphoryloxy, etc. R' is the long chain part of the titanate coupling agent molecule, which is mainly used to ensure the entanglement and miscibility with the polymer molecules, improve the impact strength of the material, reduce the surface energy of the filler, significantly reduce the viscosity of the system, and have good lubricity and rheological properties. Y is the functional group of the titanate coupling agent for cross-linking, which has unsaturated double bond groups, amino groups, hydroxyl groups, etc., and can be cross-linked with the resin. The titanate coupling agent organically modifies the surface of the inorganic material, and physically or chemically adsorbs or bonds the organic molecules to the surface of the inorganic material. This surface organic modification is divided into physical coating and chemical coating. The organic molecules coated on the surface of the filler are physically coated, thereby improving the compatibility and dispersibility of the inorganic filler in the substrate. This coating is physical coating. The coupling agent connects the filler surface and the polymer molecules in the form of chemical bonds including polar bonds. This coating method is chemical coating. The coupling agent combines the materials that were originally difficult to combine more firmly. Due to the huge difference in properties between EVA resin and biomass fiber, many gaps will appear on the bonding surface of the two phases in the microstructure, which seriously affects the performance of the composite material. However, after being treated with a coupling agent, inorganic substances such as reinforcing materials can be coupled with organic polymers, and the gaps on the bonding surface of the two phases can be reduced, so that the two phases can be firmly bonded. The coupling agent reduces the fluidity of the latex and enhances the intermolecular effect. The addition of fibers also increases the roughness of the latex surface, making the contact surface of double and triple dips of latex larger, making it easier for latex to adhere, making the latex evenly distributed and preventing slip.

[0029] 2. The resin and fiber in the resin dispersion of the hybrid fiber composite material of the present invention can promote the latex to form a gel structure. The gel has certain elasticity and stability, can prevent the flow of latex, and forms a three-dimensional structure through physical or chemical action. This structure can bind a large number of solvent molecules, so that the whole system presents a gel state. Due to the existence of the three-dimensional structure, the gel has certain stability and flexibility, can resist the action of external forces and is not easily destroyed, and can adapt to external deformation to a certain extent without breaking. Cellulose molecules contain a large number of hydroxyl groups, which can form hydrogen bonds with polar groups in resin molecules. The formation of hydrogen bonds makes cellulose and resin molecules interconnected to form a three-dimensional structure. The van der Waals force between the resin and cellulose molecules promotes the mutual attraction between the two and promotes structural stability. In addition, the resin and cellulose molecules are entangled with each other in the solution to form physical crosslinking points. These crosslinking points further enhance the stability of the gel. Covalent bonds are formed between the resin and cellulose molecules through coupling agents.

[0030] 3. The mixed cross-linking of the resin and cellulose in the present invention changes the surface tension of the latex. The appropriate surface tension can make the latex form a uniform coating on the surface of the substrate and reduce the possibility of gel flow. Cellulose is a natural polymer compound composed of glucose units and has a large number of hydroxyl groups. These hydroxyl groups can form hydrogen bonds with water molecules, so that cellulose has a certain hydrophilicity. When cellulose is mixed with resin, the hydroxyl groups of cellulose can interact with the polar groups in the resin molecules to increase the attraction between molecules, thereby increasing the surface tension. When cellulose is mixed with resin, due to the different chemical and physical properties of the two, a certain interfacial tension will be formed at the interface, thereby increasing the surface tension of the system. Cellulose and resin molecules are adsorbed at the interface due to the existence of van der Waals force to form an adsorption layer. The properties of this adsorption layer will affect the surface tension of the system, and because the molecules of cellulose and resin molecules are closely arranged and have strong interactions with the molecules in the bulk phase, the surface tension will increase.

[0031] 4. The present invention can also enhance the acid and alkali resistance of latex. Since cellulose itself has a certain chemical stability and contains a large number of hydroxyl groups in its molecular structure, these hydroxyl groups can form hydrogen bonds within and between molecules, making the cellulose molecules have a higher stability. There are crystalline regions and amorphous regions in cellulose. The cellulose molecules in the crystalline region are arranged more regularly and tightly, and the resistance to acid and alkali is relatively strong. It is difficult for acid and alkali substances to penetrate into the crystalline region, thereby protecting the core structure of cellulose. Within a certain acid and alkali range, cellulose can play a certain buffering role by adsorbing and desorbing acid and alkali ions. When the acidic substances in the environment increase, cellulose can absorb a part of hydrogen ions, thereby slowing down the damage of the acidic environment to cellulose; when the alkaline substances in the environment increase, cellulose can also absorb a part of hydroxide ions. This buffering effect can maintain the relative stability of the surrounding environment of cellulose to a certain extent, and reduce the direct impact of acid and alkali on cellulose. There may be some exchangeable ions on the surface of cellulose, such as sodium ions and calcium ions. In an acid-base environment, these ions can be exchanged with acid-base ions, thereby reducing the damage of acid and alkali to the cellulose structure. When cellulose is exposed to an acidic environment, the sodium ions on the surface can be exchanged with hydrogen ions, thereby reducing the direct attack of hydrogen ions on cellulose. When mixed with resin, the structure of cellulose can provide a certain stability basis for the entire system. Resins usually have high molecular weight and complex chemical structures, and can form a three-dimensional structure. This three-dimensional structure can effectively prevent the penetration of acid and alkali solutions, thereby improving the acid and alkali resistance of the material. The ester group and vinyl group in EVA resin are corrosion-resistant functional groups that can resist acid and alkali erosion to a certain extent. When EVA resin is mixed with cellulose, these functional groups can provide additional acid and alkali resistance to the entire material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0033] The specific implementation manner of the present invention is further described below in conjunction with the accompanying drawings, and this embodiment does not constitute a limitation of the present invention.

[0034] Example 1

[0035] like Figure 1 As shown, a method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating glove comprises the following steps:

[0036] S1, taking 20 parts of EVA resin, 5 parts of flax fiber, 5 parts of corn fiber and 2 parts of coupling agent di(octyl pyrophosphate)hydroxyacetic acid titanate and blending them to form a resin dispersion of a mixed fiber composite material;

[0037] S2, taking 80 parts of carboxyl type nitrile latex, 5 parts of resin dispersion of mixed fiber composite material, 1 part of zinc oxide, 1 part of accelerator ZDEC, 4 parts of polyacrylic acid thickener and 1 part of color paste, mixing and stirring to obtain composite latex;

[0038] S3, putting the glove core on the hand mold and preheating the glove core, specifically, placing the glove core in an oven and baking it at 70° C. for 10 minutes;

[0039] S4, dipping the preheated glove core into a coagulant, wherein the coagulant is a methanol solution containing 2% glacial acetic acid, and the coagulant dipping and homogenizing time is 60 seconds;

[0040] S5, dipping the glove core dipped in the coagulant into the first layer of composite latex for 15 seconds;

[0041] S6, after a layer of dipped glove core is left to stand for 30 minutes, the first vulcanization treatment is carried out in an oven at 60°C for 30 minutes;

[0042] S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex, the dipping time is 15s;

[0043] S8, after the two-layer dipped glove core is left to stand for 30 minutes, a second vulcanization treatment is performed in an oven at 60°C for 30 minutes;

[0044] S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex for 15 seconds;

[0045] S10, after the three-layer dipped glove core is left to stand for 30 minutes, a third high-temperature vulcanization treatment is performed in an oven at 110° C. for 1 hour;

[0046] S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

[0047] Example 2

[0048] like Figure 1 As shown, a method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating glove comprises the following steps:

[0049] S1, taking 20 parts of EVA resin, 5 parts of flax fiber, 5 parts of corn fiber and 2 parts of coupling agent di(octyl pyrophosphate)hydroxyacetic acid titanate and blending them to form a resin dispersion of a mixed fiber composite material;

[0050] S2, taking 90 parts of carboxyl type nitrile latex, 8 parts of resin dispersion of mixed fiber composite material, 2 parts of zinc oxide, 2 parts of accelerator ZDEC, 5 parts of polyacrylic acid thickener, and 1 part of color paste, and mixing and stirring to obtain composite latex;

[0051] S3, putting the glove core on the hand mold and preheating the glove core, specifically, placing the glove core in an oven and baking it at 60° C. for 12 minutes;

[0052] S4, dipping the preheated glove core into a coagulant, wherein the coagulant is a methanol solution containing 5% glacial acetic acid, and the coagulant dipping and homogenizing time is 70 seconds;

[0053] S5, dipping the glove core dipped in the coagulant into the first layer of composite latex for 15 seconds;

[0054] S6, after a layer of dipped glove core is left to stand for 30 minutes, the first vulcanization treatment is carried out in an oven at 60°C for 30 minutes;

[0055] S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex, the dipping time is 15s;

[0056] S8, after the two-layer dipped glove core is left to stand for 30 minutes, a second vulcanization treatment is performed in an oven at 60°C for 30 minutes;

[0057] S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex for 15 seconds;

[0058] S10, after the three-layer dipped glove core is left to stand for 30 minutes, a third high-temperature vulcanization treatment is performed in an oven at 110° C. for 1 hour;

[0059] S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

[0060] Example 3

[0061] like Figure 1 As shown, a method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating glove comprises the following steps:

[0062] S1, taking 20 parts of EVA resin, 5 parts of flax fiber, 5 parts of corn fiber and 2 parts of coupling agent di(octyl pyrophosphate)hydroxyacetic acid titanate and blending them to form a resin dispersion of a mixed fiber composite material;

[0063] S2, taking 100 parts of carboxyl type nitrile latex, 12 parts of resin dispersion of mixed fiber composite material, 2 parts of zinc oxide, 3 parts of accelerator ZDEC, 6 parts of associative thickener, and 1 part of color paste, mixing and stirring to obtain composite latex;

[0064] S3, putting the glove core on the hand mold and preheating the glove core, specifically, placing the glove core in an oven and baking it at 60° C. for 12 minutes;

[0065] S4, dipping the preheated glove core into a coagulant, wherein the coagulant is a methanol solution containing 5% glacial acetic acid, and the coagulant dipping and homogenizing time is 70 seconds;

[0066] S5, dipping the glove core dipped in the coagulant into the first layer of composite latex for 20 seconds;

[0067] S6, after a layer of dipped glove core is left to stand for 30 minutes, the first vulcanization treatment is carried out in an oven at 60°C for 30 minutes;

[0068] S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex, the dipping time is 20 seconds;

[0069] S8, after the two-layer dipped glove core is left to stand for 30 minutes, a second vulcanization treatment is performed in an oven at 60°C for 30 minutes;

[0070] S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex for 20 seconds;

[0071] S10, after the three-layer dipped glove core is left to stand for 30 minutes, a third high-temperature vulcanization treatment is performed in an oven at 100°C for 1.5 hours;

[0072] S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

[0073] Example 4

[0074] like Figure 1 As shown, a method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating glove comprises the following steps:

[0075] S1, taking 20 parts of EVA resin, 5 parts of flax fiber, 5 parts of corn fiber and 2 parts of coupling agent di(octyl pyrophosphate)hydroxyacetic acid titanate and blending them to form a resin dispersion of a mixed fiber composite material;

[0076] S2, taking 110 parts of carboxyl type nitrile latex, 15 parts of resin dispersion of mixed fiber composite material, 3 parts of zinc oxide, 2 parts of accelerator ZDEC, 6 parts of associative thickener, and 2 parts of color paste, mixing and stirring to obtain composite latex;

[0077] S3, putting the glove core on the hand mold and preheating the glove core, specifically, placing the glove core in an oven and baking it at 60° C. for 12 minutes;

[0078] S4, dipping the preheated glove core into a coagulant, wherein the coagulant is a methanol solution containing 1% calcium chloride, and the coagulant dipping and homogenizing time is 80 seconds;

[0079] S5, dipping the glove core dipped in the coagulant into the first layer of composite latex for 20 seconds;

[0080] S6, after a layer of dipped glove core is left to stand for 30 minutes, the first vulcanization treatment is carried out in an oven at 60°C for 30 minutes;

[0081] S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex, the dipping time is 20 seconds;

[0082] S8, after the two-layer dipped glove core is left to stand for 30 minutes, a second vulcanization treatment is performed in an oven at 60°C for 30 minutes;

[0083] S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex for 20 seconds;

[0084] S10, after the three-layer dipped glove core is left to stand for 30 minutes, a third high-temperature vulcanization treatment is performed in an oven at 100°C for 1.5 hours;

[0085] S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

[0086] Example 5

[0087] like Figure 1 As shown, a method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating glove comprises the following steps:

[0088] S1, taking 20 parts of EVA resin, 5 parts of flax fiber, 5 parts of corn fiber and 2 parts of coupling agent di(octyl pyrophosphate)hydroxyacetic acid titanate and blending them to form a resin dispersion of a mixed fiber composite material;

[0089] S2, taking 120 parts of carboxyl type nitrile latex, 18 parts of resin dispersion of mixed fiber composite material, 3 parts of zinc oxide, 3 parts of accelerator ZDEC, 6 parts of thickener hydroxymethyl cellulose, and 2 parts of color paste, and mixing and stirring to obtain composite latex;

[0090] S3, putting the glove core on the hand mold and performing preheating treatment, specifically, placing the glove core in an oven and baking it at 50° C. for 15 minutes;

[0091] S4, dipping the preheated glove core into a coagulant, wherein the coagulant is a methanol solution containing 2% calcium chloride, and the coagulant dipping and homogenizing time is 90 seconds;

[0092] S5, dipping the glove core dipped in the coagulant into the first layer of composite latex for 25 seconds;

[0093] S6, after a layer of dipped glove core is left to stand for 30 minutes, the first vulcanization treatment is carried out in an oven at 60°C for 30 minutes;

[0094] S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex, the dipping time is 25 seconds;

[0095] S8, after the two-layer dipped glove core is left to stand for 30 minutes, a second vulcanization treatment is performed in an oven at 60°C for 30 minutes;

[0096] S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex, the dipping time is 25 seconds;

[0097] S10, after the three-layer dipped glove core is left to stand for 30 minutes, a third high-temperature vulcanization treatment is performed in an oven at 80°C for 2 hours;

[0098] S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

[0099] Example 6

[0100] like Figure 1 As shown, a method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating glove comprises the following steps:

[0101] S1, taking 20 parts of EVA resin, 5 parts of flax fiber, 5 parts of corn fiber and 2 parts of coupling agent di(octyl pyrophosphate)hydroxyacetic acid titanate and blending them to form a resin dispersion of a mixed fiber composite material;

[0102] S2, taking 120 parts of carboxyl type nitrile latex, 20 parts of resin dispersion of mixed fiber composite material, 4 parts of zinc oxide, 4 parts of accelerator ZDEC, 6 parts of thickener hydroxymethyl cellulose, and 2 parts of color paste, mixing and stirring to obtain composite latex;

[0103] S3, putting the glove core on the hand mold and performing preheating treatment, specifically, placing the glove core in an oven and baking it at 50° C. for 15 minutes;

[0104] S4, dipping the preheated glove core into a coagulant, wherein the coagulant is a methanol solution containing 2% calcium chloride, and the coagulant dipping and homogenizing time is 90 seconds;

[0105] S5, dipping the glove core dipped in the coagulant into the first layer of composite latex for 25 seconds;

[0106] S6, after a layer of dipped glove core is left to stand for 30 minutes, the first vulcanization treatment is carried out in an oven at 60°C for 30 minutes;

[0107] S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex, the dipping time is 25 seconds;

[0108] S8, after the two-layer dipped glove core is left to stand for 30 minutes, a second vulcanization treatment is performed in an oven at 60°C for 30 minutes;

[0109] S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex, the dipping time is 25 seconds;

[0110] S10, after the three-layer dipped glove core is left to stand for 30 minutes, a third high-temperature vulcanization treatment is performed in an oven at 80°C for 2 hours;

[0111] S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

[0112] Comparative Example 1

[0113] A method for preparing a three-layer dipped chemical-resistant coating glove comprises the following steps:

[0114] S1, taking 80 parts of carboxyl type nitrile latex, 1 part of zinc oxide, 1 part of accelerator ZDEC, 4 parts of polyacrylic acid thickener and 1 part of color paste, mixing and stirring to obtain a composite latex;

[0115] S2, putting the glove core on the hand mold and preheating the glove core, specifically, placing the glove core in an oven and baking it at 70° C. for 10 minutes;

[0116] S3, dipping the preheated glove core into a coagulant, wherein the coagulant is a methanol solution containing 2% glacial acetic acid, and the coagulant dipping and homogenizing time is 60 seconds;

[0117] S4, dipping the glove core dipped in the coagulant into the first layer of composite latex for 15 seconds;

[0118] S5, after a layer of dipped glove core is left to stand for 30 minutes, the first vulcanization treatment is carried out in an oven at 60°C for 30 minutes;

[0119] S6, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex, the dipping time is 15s;

[0120] S7, after the two-layer dipped glove core is left to stand for 30 minutes, a second vulcanization treatment is performed in an oven at 60°C for 30 minutes;

[0121] S8, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex, the dipping time is 15s;

[0122] S9, after the three-layer dipped glove core is left to stand for 30 minutes, a third high-temperature vulcanization treatment is performed in an oven at 110°C for 1 hour;

[0123] S10, demoulding, and obtaining a three-layer dipped chemical resistant coated glove.

[0124] The gloves prepared in Examples 1 to 6 and Comparative Example 1 were subjected to performance tests in accordance with the requirements of EN374 standard. The test results are shown in Table 1 below.

[0125] Table 1 Glove performance test data of each embodiment

[0126]

[0127] It can be seen from the above experimental data that the use of a unique modified biomass composite material in the formula in the embodiment ensures that the long-tube gloves maintain a relatively slow fluidity when the gloves are dipped at a uniform speed. In the specific preparation process, the slippage phenomenon that is easy to occur between the rubber layers when the gloves are dipped is well solved. Shear thinning does not occur under high shearing action such as high-speed stirring, and the stability of the rubber material is always maintained, thereby improving the appearance smoothness of the gloves. To a certain extent, the more the modified composite material is added, the more excellent the chemical resistance performance of the latex is improved. The two together ensure that the performance of the gloves is much better than that of traditional gloves. The long-tube chemical-resistant gloves of the present invention can meet the chemical resistance function in most occasions while considering both wear resistance and chemical resistance, and at the same time have both comfort and flexibility for long-term wearing.

[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions should also be deemed to fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing anti-slip rubber biomass modified three-layer dipped chemical protective coating gloves, characterized in that: The steps include: S1, blending EVA resin, biomass fiber and coupling agent to form a resin dispersion of a mixed fiber composite material; S2, mixing butadiene-acrylonitrile latex, a resin dispersion of a mixed fiber composite material, zinc oxide, an accelerator, a thickener and a color paste to obtain a composite latex; S3, taking the glove core and putting it on the hand mold for preheating; S4, dipping the preheated glove core into a coagulant; S5, dipping the glove core dipped in the coagulant into the first layer of composite latex; S6, after a layer of dipped glove core is left to stand, the first vulcanization treatment is performed in an oven; S7, taking the glove core after the first vulcanization treatment and dipping it into the second layer of composite latex; S8, after the two-layer dipped glove core is left to stand, a second vulcanization treatment is performed in an oven; S9, taking the glove core after the second vulcanization treatment and dipping it into the third layer of composite latex; S10, after the three-layer dipped glove core is left to stand, a third high-temperature vulcanization treatment is performed in an oven; S11, demoulding, and obtaining the anti-slip rubber biomass modified three-layer dipped chemical resistant coating gloves.

2. The method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating gloves according to claim 1, characterized in that: The biomass fibers in S1 include flax fibers and corn fibers, the coupling agent is a chelated titanate, specifically di(octyl pyrophosphate)hydroxyacetic acid titanate, and the mass proportions of raw materials added to the resin dispersion of the mixed fiber composite material are: 5-20 parts of EVA resin, 1-10 parts of flax fibers, 1-10 parts of corn fibers and 1-5 parts of coupling agent.

3. The method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating gloves according to claim 1, characterized in that: The nitrile latex in S2 is carboxyl nitrile latex, the thickener is a polyacrylic thickener or an associative thickener or hydroxymethyl cellulose or a mixture of the first three in any proportion, the accelerator is ZDEC, and the mass proportions of the raw materials in the composite latex are: 80-120 parts of nitrile latex, 1-20 parts of resin dispersion of mixed fiber composite material, 1-4 parts of zinc oxide, 1-5 parts of accelerator, 4-6 parts of thickener, and 1-2 parts of color paste.

4. The method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating gloves according to claim 1, characterized in that: The specific operation of the preheating treatment in S3 includes: placing the glove core in an oven at 50-70° C. and baking for 10-15 minutes.

5. The method for preparing a non-slip biomass modified three-layer dipped chemical-resistant coating gloves according to claim 1, characterized in that: The coagulant in S4 is a methanol solution containing 1-5% glacial acetic acid or 1-2% calcium chloride, and the coagulant immersion and homogenization time is 60-90s.

6. The method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating gloves according to claim 1, characterized in that: The time for dipping the first layer of composite latex, the second layer of composite latex and the third layer of composite latex in S5, S7 and S9 is 15-25 seconds.

7. The method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating gloves according to claim 1, characterized in that: The standing time of the rubber-dipped glove core in S6 and S8 is 30 minutes, and the first vulcanization treatment and the second vulcanization treatment are specifically vulcanization in an oven at 60° C. for 30 minutes.

8. The method for preparing a non-slip rubber biomass modified three-layer dipped chemical-resistant coating gloves according to claim 1, characterized in that: The three-layer dipped glove core in S10 is left standing for 30 minutes, and the third high-temperature vulcanization treatment is specifically vulcanization in an oven at 80-110° C. for 1-2 hours.

Citation Information

Cited By

  • Glove with high chemical defense performance and preparation method

    CN120814699A